Enhancing Adsorption Efficiency of Cd Heavy Metal Ions using Aceh's Natural Bentonite: A Design Expert 13 Optimization Study - Jakfar Jakfar; Azwar Azwar (Jurnal Serambi Engineering, 2023)
Wastewater containing heavy metal ions presents a formidable challenge to environmental sustainability because heavy metals are nonbiodegradable and toxic. Cadmium has been identified by scientific consensus as one of the most perilous and deleterious chemicals. These metal ions have a significant effect on many illnesses in living organisms, including humans. Therefore, an effective absorption technique is required to mitigate the issues caused by this waste. Adsorption is frequently used to remediate heavy metal waste and improve the processing process because of its versatility and suitability as a technology. The principal aim of this investigation was to augment the adsorptive potency of cadmium (Cd) ions by optimizing the utilization of natural Aceh bentonite. The optimization process utilizes Design Expert 13, specifically Box Behnken Design with Response Surface Methodology. The results of the optimization revealed the significance of bentonite mass (1-2 g), stirring time (30-200 minutes), and initial Cd adsorbate concentration (100-500 mg/l) on the absorption of Cd (II) ions. Optimal conditions for Cd (II) ion adsorption by Aceh natural bentonite were achieved with an agitation time of 2 mass, 126.8 minutes of agitation time, and Cd (II) ion concentration of 500 mg/l. Under these conditions, the adsorption of Cd (II) ions by Aceh natural bentonite was 220.5 mg/l, and the desirability of this outcome was 0.84.